Strategic Leadership and Digital Transformation: Enhancing Organizational Agility in the Post-Pandemic Era - Nasution, Siti Ummi Arfah (PT Inovasi Pratama Internasional, 2024)
The COVID-19 pandemic has fundamentally transformed organizational landscapes, accelerating digital transformation initiatives and highlighting the critical importance of organizational agility. This study examines the relationship between strategic leadership, digital transformation, and organizational agility in the Indonesian business context during the post-pandemic era. Using a mixed-methods approach combining quantitative surveys (n=284) with qualitative in-depth interviews (n=32), this research investigates how strategic leadership capabilities facilitate digital transformation and enhance organizational agility. The study employs transformational leadership theory, upper echelons theory, and dynamic capabilities framework to understand the mechanisms through which leadership drives organizational change. Findings reveal that strategic leadership significantly mediates the relationship between digital transformation initiatives and organizational agility, with Indonesian organizations demonstrating unique adaptation patterns influenced by cultural and contextual factors. The research contributes to leadership and organizational change literature by providing empirical evidence of how strategic leaders navigate digital transformation challenges while building organizational resilience. Practical implications suggest that organizations must develop adaptive leadership capabilities, invest in digital literacy, and create flexible organizational structures to thrive in the post-pandemic business environment.